PENGARUH MEDIA EDMODO TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 INDRALAYA UTARA - Eka Rahmawati; Riswan Jaenudin; Fitriyanti Fitriyanti (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2015)
This study aims to determine the effect Edmodo media on learning outcomes of students in economic subjects in SMAN 1 North Indralaya. This research included in this type of experimental study design form one group pretest - posttest design. The study population was all students of class X IPS SMAN 1 North Indralaya consisting of two odd semester classes 2014-2015 totaling 62 learners. Samples were taken using cluster random sampling technique, and didapatlah class as a class X IPS 2 samples with the number of students as many as 32 people. Data collection techniques using tests and observation. The statistics are used to analyze the data is using t-test with df = n-2 level signifikat (α = 0.05). Based on tests performed data analysis, t-test results showed that the value of t = 5.4537> table = 1.697. Thus in this study Ho rejected and Ha accepted that there is influence that social media signifikat Edmodo to the learning outcomes of students. The mean learning outcomes of students increased from 44.12 into 86.40. Therefore, it is advisable for teachers to use the media Edmodo as one alternative to improve the learning outcomes of students.